Remote sensing of ocean colour: Towards algorithms for retrieval of pigment composition - Sathyendranath, S; Stuart, V; Platt, T; Bouman, H; Ulloa, O; Maass, H (2005)
Ocean colour varies as an inverse function of the absorption coefficient. In Case 1 waters, phytoplankton are known to be the principal agents responsible for variations in the total absorption coefficient. The concentration and composition of pigments present have a strong influence on phytoplankton absorption spectra. Empirical (regression) algorithms exist to recover the wavelength-specific absorption coefficient of phytoplankton from the concentration of the main pigment, chlorophyll-a. However, to explain the residuals about such regressions remains a major challenge. We have analysed a set of over 1,600 absorption spectra of phytoplankton collected from various oceanographic provinces. In parallel, we examined the corresponding pigment complexes, as revealed by High Performance Liquid Chromatography (HPLC). We have uncovered broad trends in the shapes of the absorption spectra and in the pigment complexes, consequent upon changes in the pigment biomass, with clear implications for the remote sensing of ocean colour.